2016
DOI: 10.1016/j.evolhumbehav.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for quantity–quality trade-offs, sex-specific parental investment, and variance compensation in colonized Agta foragers undergoing demographic transition

Abstract: Evolutionary ecological models of human fertility predict that (1) parents will bias investment toward the sex with the highest fitness prospects in a particular socio-ecological context; (2) fertility is subject to quantity-quality trade-offs; and (3) fertility decisions will be sensitive to both predictable and stochastic mortality risk and the relative fitness value of differently sized sib-sets (the variance compensation hypothesis). We test these predictions using demographic records from the Agta, an ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Life history trade-offs and (adaptive) physiological mechanisms are considered essential to an understanding of how reproduction is regulated (Voland 1998), but we do not consider physiological mechanisms explicitly here (see Ellison 1994). In addition, although our focus is exclusively on fertility among industrialized populations, many of our points hold equally well (sometimes even more so) for nonindustrial populations, ranging from small-scale societies to “transitioning” populations (e.g., Alvergne et al 2013; Bolund et al 2015; Colleran et al 2014; Gibson and Lawson 2014; Moorad 2013; Ross et al 2016; Shenk et al 2013). A number of the other articles in this special issue also attest to this.…”
mentioning
confidence: 73%
“…Life history trade-offs and (adaptive) physiological mechanisms are considered essential to an understanding of how reproduction is regulated (Voland 1998), but we do not consider physiological mechanisms explicitly here (see Ellison 1994). In addition, although our focus is exclusively on fertility among industrialized populations, many of our points hold equally well (sometimes even more so) for nonindustrial populations, ranging from small-scale societies to “transitioning” populations (e.g., Alvergne et al 2013; Bolund et al 2015; Colleran et al 2014; Gibson and Lawson 2014; Moorad 2013; Ross et al 2016; Shenk et al 2013). A number of the other articles in this special issue also attest to this.…”
mentioning
confidence: 73%
“…Measures of life-history trade-offs should accordingly incorporate currencies earned through sexual selection. This will produce a more fully unified evolutionary account of fertility that includes social and institutional considerations and constraints [ 114 , 115 ]. For example, there is good reason to believe that mating dynamics play an important role in human fertility variation, in so far as both the age at which individuals enter marriage and the rate at which they change or accumulate mates vary widely across and within populations.…”
Section: Beyond the Quantity–quality Trade-offmentioning
confidence: 99%
“…Son-preference is perhaps most evident in some East and South Asian societies (Das Gupta et al 2003;Murphy et al 2011), but has also been widely reported in sub-Saharan Africa (Campbell, 1991;Fayehun et al, 1997;Frempong and Codjoe 2017). Parental biases favouring sons will be adaptive when the marginal returns to investing in sons is greater than for daughters (Keller et al 2001;Ross et al 2016;Veller et al 2016). This scenario may especially characterize contexts where variability in male fitness is extended via polygynous marriage so that successful males obtain particularly high reproductive success (Clutton- Brock et al 1981;Leimar, 1996;Irwin et al 2006; but see Brown et al 2009).…”
Section: Introductionmentioning
confidence: 94%